The Role of Islamic Economics on Covid-19 Recovery: A Text Analytics - Aisyah As-Salafiyah (Islamic Economics Methodology, 2022)
This text analytics research investigates the current state of various studies on the role of Islamic economics during the COVID-19 pandemic published by Scopus indexed journals. The analysis is focused on the description of the characteristics and trends of the keywords. The data analyzed were 51 research publications on the theme of Islamic economics during the COVID-19 pandemic. The search used to define the research dataset was last updated on August 7, 2021. Descriptive statistical methods were used, and text analytics was performed using R Biblioshiny to discover the mapping of text analytics. The number of articles discussing Islamic economics during the COVID-19 pandemic is quite significant in the scientific literature. Many keywords were used in the research of this theme, of which the most popular was 'COVID-, Islamic, Financial'. This research provides a text analytics overview of the most popular keyword trends with the role of Islamic economics during the COVID-19 pandemic, thereby providing information for researchers who focus on research in this field. This study also examines the Islamic economic instruments used in dealing with the impact of the COVID-19 pandemic and the role of each instrument. In the end, this theme has the potential to continue to be developed.